Identitas Baru Suku Pedalaman Ta’a Wana Pasca Pengucapan Syahadat di Desa Wenangabino Morowali Utara - Pensed, Fitri; Petta Solong, Najamuddin; Manahung, Muh. Ramoend (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The problem of this research is focused on the reality related to the new identity possessed by the Ta'a Wana hinterland tribe after the pronunciation of two sentences of shahada and the purpose of this study is to identify the new identity that has undergone a shift after the pronunciation of shahada both from Spiritual, Material, and Immaterial aspects that occurred in Wenangabino Village North Morowali Indonesia. This research method is qualitative with a phenomenological approach. Data sources are primary and secondary sources. Data collection methods are observation, interviews and documentation. The research instrument is the researcher himself. Data analysis includes data reduction, data presentation, and conclusions. Data validity testing consists of extended participation, observational persistence, and triangulation. The results of the study showed a shift in spiritual, material, and immaterial identities after the pronunciation of the shahada for the Ta'a Wana hinterland tribe, for example in spiritual identity began to maintain cleanliness, cover the aurat, say thayibah sentences, eat halal food, limit association derived from Islamic values. Similarly, material identity is no longer tribal fanatics because it has been bound by religious similarities, and immaterial identity that prioritizes social ethics in responding to the existence of customary and religious institutions.